Protective effects of metabolites from lactic acid bacteria against infections of mastitis pathogen in bovine cells - Thida Kaewkod; Nitsanat Cheepchirasuk; Sureeporn Suriyaprom; Witaya Suriyasathaporn; Thararat Chitov; Aussara Panya; Yingmanee Tragoolpua (Scientific Reports)
Abstract Bovine mastitis poses significant economic challenges for dairy farms globally. Metabolites from lactic acid bacteria (LAB) offer promising alternative substances for preventing bovine mastitis. This study demonstrated the inhibitory activity of metabolite production from seven LAB isolates in the supernatant medium. Four isolates, namely Lactiplantibacillus plantarum TISTR 2070, Lacticaseibacillus casei TISTR 1340, Enterococcus faecalis TCAN02, and Lactiplantibacillus plantarum AD73, exhibited antibacterial activity against bacterial pathogens causing mastitis, including Staphylococcus haemolyticus, Staphylococcus capitis subsp. ureolyticus, Streptococcus agalactiae O4, Streptococcus dysgalactiae, and Streptococcus uberis. The minimum inhibitory concentration (MIC) values ranged from 6.25 to 25 mg/mL, with minimum bactericidal concentration (MBC) values of 12.5 to 25 mg/mL. Furthermore, analysis of the physical and chemical properties revealed active metabolites in LAB supernatants, particularly lactic acid that was detected in all samples. Additionally, this study presents novel findings on infection of CPAE bovine endothelial cells in vitro by mastitis bacterial pathogens and demonstrating cytopathic effects such as vacuolation, magalocytosis, and cytotoxicity after bacterial infection on the bovine endothelial cells. Moreover, metabolites from LAB supernatant exhibited a protective effect against bacterial colonization and infection of bacterial pathogens causing mastitis on CPAE bovine endothelial cells and leading to increase cell viability. The results of this study suggest that metabolites from LAB samples exert potential candidates as alternative therapeutic agents for bovine mastitis.